Peranan Kepala Perpustakaan Dalam Mendorong Kenaikan Pangkat/ Jabatan Fungsional Pustakawan Di Dinas Perpustakaan Dan Arsip Daerah Provinsi Jambi - Rapita, Rapita; Haqqi, Athiatul; Yusufhin, Fridinanti (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT Introduction. The purpose of this research is to find out how the role of the Head of the Library in encouraging the promotion / functional position of librarian in the Regional Library and Archives Service of Jambi Province and to find out what are the factors that hinder the promotion and functional position of librarian as well as the efforts of the Head of Librarian in encouraging promotion. and librarian functional positions at the Regional Library and Archives Office of Jambi Province. Data Collection Method. This study used a descriptive qualitative method with a purposive sampling approach. Result and Discussion. The results of this study indicate that the role of the Head of the Library in encouraging the promotion / functional position of librarian in the Regional Library and Archives Service of Jambi Province has not fully provided a role, especially for librarians who have problems collecting credit numbers and are late in promotion / functional librarian position. Inhibiting factors in promotion / functional position of librarian caused by: 1). The assessment team who sometimes judges are not objective in providing value. 2). Differences in perceptions between the assessment team in assessing the physical evidence of librarians. 3). The assessment team's draft was issued late. 4). Librarian functional officers do not understand how to fill out the DUPAK correctly. 5). Librarian functional officers are less creative or lazy to collect credit scores. 6). Workload that does not match the number of librarians. The effort of the Head of the Library in encouraging promotion and functional position of librarian at the Regional Library and Archives Service of Jambi Province is to be temporarily suspended from the Librarian Functional Position if it is 5 years late to collect credit figures, besides that it will also be transferred to a structural position. Another effort is planning this year to hold a DUPAK preparation workshop which aims to enable librarians to be able and know how to properly compile DUPAK based on JUKNIS. Conclusions. 1). It is expected that the Head of Service will pay attention to the librarian functional officials. 2). It is hoped that the assessment team can provide values transparently and fairly. 3). It is hoped that it can create an activity program aimed at motivating librarians in collecting credit scores